Molecular Markers of Sulfadoxine-Pyrimethamine Resistance in Samples from Children with Uncomplicated Plasmodium falciparum at Three Sites in Angola in 2019 - Rosillo, Stefano R. (2023)
Funding Information: The study was funded by the U.S. President’s Malaria Initiative and the Advanced Molecular Detection program at CDC. Funding Information: We thank all study staff and participants, Venceslau Mambi Pelenda, José Bumba da Cunha, Oliveira Kiatoko, Felismina Caquece, Luzala Elisabeth Armando Garcia, Djos Kialanda, Garcia Pembele, Domingos Jandondo, and Belmira José Bondo. The findings and conclusions in this report are those of the author(s) and do not necessarily represent the official position of the U.S. Centers for Disease Control and Prevention or the U.S. Agency for International Development. The study was funded by the U.S. President’s Malaria Initiative and the Advanced Molecular Detection program at CDC. P.R.D., C.M.F., B.N.A., S.L., R.H., J.F.M.M., F.F., J.F.M., and M.M.P. designed and participated in the specimen collection. P.R.D., A.L.M.C., S.R.R., and J.K. performed the laboratory analysis. P.R.D., A.L.M.C., J.K., S.R.R., J.-H.M.O., and E.T. analyzed the sequencing data. S.R.R. and M.M.P. wrote the manuscript. All authors read and approved the final version of the manuscript. Publisher Copyright: Copyright © 2023 Rosillo et al.